(In)Essential Bordering: Canada, COVID, and Mobility - Macklin, Audrey (Frontiers in Human Dynamics, 2020)
The global migration of COVID-19 not only disrupted transborder movement. In many (if not most) states, statis and closure became the default norm at and within borders. This, in turn, generated exceptions organized around an idea of ‘essential’ entry. The category of ‘essential’ was produced, revised, and represented through the interaction of pandemic-driven exigencies and nationally specific articulations of the legal, political, and economic constraints in play. To understand how the admission into Canada of certain people was accepted as legally, economically and/or politically essential, one must take account of Canada’s character as a settler society, its economic integration with the United States, and its growing dependence on migrant workers and international students to subsidize food production and higher education for nationals.